3D Thioether‐Based Covalent Organic Frameworks for Selective and Efficient Mercury Removal. Issue 22 (19th February 2021) - Zhang, Yiying; Li, Hui; Chang, Jianhong; Guan, Xinyu; Tang, Lingxue; Fang, Qianrong; Valtchev, Valentin; Yan, Yushan; Qiu, Shilun
Abstract: Developing functionalized 3D covalent organic frameworks (3D COFs) is critical to broaden their potential applications. However, the introduction of specific functionality in 3D COFs remains a great challenge because most of the functional groups are not compatible with the synthesis conditions. Herein, for the first time 3D thioether‐based COFs (JUC‐570 and JUC‐571) for mercury (Hg 2+ ) removal from aqueous solution is reported. These 3D thioether‐based COFs prepared by the bottom‐up approach display high Hg 2+ uptakes (972 mg g −1 for JUC‐570 and 970 mg g −1 for JUC‐571 at pH = 5), fast adsorption kinetics (distribution coefficient Kd value of 2.29 × 10 7  mL g −1 for JUC‐570 and 2.07 ×  10 7  mL g −1 for JUC‐571), and favorable selectivity. In particular, JUC‐570 is periodically decorated with isopropyl groups around imine bonds that markedly improve its chemical stability and effectively prevent the pore collapse, and thus endows high Hg 2+ adsorption capacity (619 mg g −1 ) and excellent cycle performance even at pH = 1. This study not only puts forward a new route to construct stable functionalized 3D COFs, but also promotes their potential applications in areas related to the environment. Abstract : 3D thioether‐based COFs, JUC‐570 and JUC‐571, are for the first time prepared by the bottom‐up approach, and used for mercury (Hg 2+ ) removal from aqueous solution. In particular, JUC‐570 is periodically decorated with isopropyl groups around imine bonds, which displays higher chemical stability, BET specific surface area, and Hg 2+ removal performance.